Generalized-Disturbance Rejection Control for Vibration Suppression of Piezoelectric Laminated Flexible Structures - Xiao-Yu Zhang; Run-Xiao Wang; Shun-Qi Zhang; Zhan-Xi Wang; Xian-Sheng Qin; Rüdiger Schmidt (Shock and Vibration)
In the framework of disturbance rejection (DR) control, the paper proposes a generalized-disturbance rejection (GDR) control with proportional-integral (PI) observer for vibration suppression of smart structures under any unknown continuous disturbances. In the proposed GDR-PI control, a refined state space model is first constructed, and a generalized disturbance including the disturbance influence matrices, unknown physical disturbances, and state variables is defined. In the closed loop of GDR-PI control, physical disturbances can be counteracted indirectly by feeding back estimated generalized disturbances. By this means, the GDR-PI control remedies most of the defects in conventional DR control and has excellent performances especially in the following situations: (i) the disturbances are completely unknown; (ii) the number of sensor signals is less than the number of disturbances; (iii) the unknown disturbances vary fast. Finally, the GDR-PI control is validated and compared with H∞ state feedback control and conventional DR control available in the literature for vibration suppression of smart beams.